Are Females at Greater Risk for Revision Surgery After Hip Resurfacing Arthroplasty With the Articular Surface Replacement Prosthesis?. Issue 10 (October 2016) - Donahue, Gabrielle S.; Lindgren, Viktor; Galea, Vincent P.; Madanat, Rami; Muratoglu, Orhun; Malchau, Henrik
Abstract: Background: Female patients undergoing hip resurfacing arthroplasties may be at greater risk of revision surgery than males, but it is unclear whether this is related to sex or other factors. We focused our analysis on data from a prospective multicenter cohort study monitoring the ASR TM hip resurfacing arthroplasty prosthesis on the potential association of sex on patient‐reported outcome measures (PROMs), metal ion levels, revision surgery, and presence of adverse local tissue reaction. As thousands of patients with the ASR TM prosthesis are still undergoing followup it is critical to optimize the protocol for monitoring these patients. Questions/purposes: We wished (1) to assess the associations between sex and implant survival, and adverse local tissue reaction; and (2) to report the differences between sexes in metal ion levels and patient‐reported outcome measures. Methods: One thousand two hundred fifty‐two patients (1390 hips) who underwent hip resurfacing arthroplasty with implantation of the ASR TM prosthesis from April 2003 to July 2010 were eligible for enrollment in a multicenter followup study of the ASR TM Hip Resurfacing System after the voluntary recall of this device was initiated by DePuy in 2010. Nine hundred seventy patients (1098 hips) were enrolled at a mean of 7 years after surgery, with a mean followup of 2 years (range, 1‐3.5 years). Nine hundred fifty‐eight patients (1084 hips) met the inclusion criteria: ability to provide informed consent, complete PROMs, and continued routine followup. A subset of patients (150 patients, 171 hips), who all were from one center, with annual metal artifact reduction sequence MRI were analyzed. Ninety‐three percent of patients from this center had routine MRI performed. The EuroQoL (EQ‐5D), Harris hip score (HHS), University of California Los Angeles (UCLA) activity score, VAS pain, radiographs, patient and surgery details, and blood cobalt and chromium levels were obtained. Cox regression analysis was conducted to identify factors associated with implant survival, using any revision as the end point, and presence of adverse local tissue reaction. Results: In patients who had unilateral surgery, the only variable found to be associated with revision surgery was HHS (hazard ratio [HR], 0.96; 95% CI, 0.94‐0.97; p < 0.001). In patients who had bilateral surgery, only HHS (HR, 0.93; 95% CI, 0.90‐0.97; p < 0.001) and cobalt level (HR, 1.02; 95% CI, 1.01‐1.03; p < 0.001) were associated with risk for revision. In patients with metal artifact reduction sequence MRI, the only variable found to be associated with presence of adverse local tissue reaction was cobalt level (HR, 1.06; 95% CI, 1.02‐1.10; p = 0.001). Cobalt and chromium concentrations were greater in female patients than in male patients (cobalt, median 1.89 versus median 1.12 parts per billion [ppb], p < 0.001; chromium, median 2.03 versus median 1.17 ppb, p < 0.001). Slight differences were observed between males and females in HHS (males median 96 versus females median 94, p < 0.001) and UCLA scores (median 8 versus median 6, p < 0.001); however, there was no difference between sexes for VAS pain (median 0.5 versus median 0.5, p = 0.405). Differences were identified between males and females in the distribution of EQ‐5D scores, yet the medians were the same (median 1.0 versus median 1.0, p < 0.001). Conclusions: Male and female patients who had hip resurfacing arthroplasty with implantation of the ASR TM prosthesis should be followed with equal vigilance as both are at similar risk of revision surgery and adverse local tissue reaction. Metal ion levels and HHS should be obtained at followup to monitor for risk of revision and as a screening tool for MRI. Further research is necessary to evaluate if these relationships persist in patients with other metal‐on‐metal prostheses. Level of Evidence: Level II, therapeutic study.